Tumor-infiltrating immune cells state-implications for various breast cancer subtypes - Xu, Tianshuang; Zhang, Hongjun; Yang, Burton B.; Qadir, Javeria; Yuan, Hui; Ye, Ting (Frontiers in Immunology, 2025)
Breast cancer presents a variety of subtypes due to its cellular and molecular heterogeneity. The capacity of cancer cells to proliferate, invade, and metastasize depends not only on their intrinsic characters but also on their dynamic interaction with the host tumor microenvironment (TME), which includes immune cells. Meanwhile, the infiltration of immune cells in the TME severely affects the occurrence, development, treatment, and prognosis of breast cancer. Therefore, this review aims to explore the immune invasive tumor microenvironment in different intrinsic subtypes of breast cancer. Additionally, it highlights the mechanistic influence of the infiltrating immune cells on stage-wise dynamics of breast tumorigenesis. Moreover, the present review also attempts to discern the regulatory relationship between tumor infiltrating immune cells and immune microenvironment in different molecular subtypes of breast cancer, thus, spotlighting its clinical significance.